Recent advances in bioactive pyrazoles - ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2015)
Pyrazole is a five membered and two-nitrogen containing heterocyclic ring. These structures have been investigated in the development of novel compounds with hypoglycemic, analgesic, anti-inflammatory, antimicrobial, anticonvulsant, antidepressant, antimycobacterial, antioxidant, antiviral, insecticidal and antitumor activities. Therefore, these compounds have been synthesized as target structures by many researchers and were evaluated for their biological activities. We hope that the bioactivity of pyrazole derivatives will be beneficial for the rational design of new generation of small molecule drugs. In this review, we report the structures of 1H-pyrazoles with their corresponding biological activities for 21st (in 2000-2014 years) century. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Pyrazole; Biological activity; Antipyrine; Celecoxib; Pyrazofurin; Fipronil; LUNG-CANCER CELLS; SELECTIVE COX-2 INHIBITORS; INFLAMMATORY-ANTIMICROBIAL AGENTS; RESISTANT STAPHYLOCOCCUS-AUREUS; ANTI-HCV AGENTS; BIOLOGICAL EVALUATION; ANTIINFLAMMATORY AGENTS; MOLECULAR DOCKING; ANTICANCER AGENTS; IN-VITRO